A Review on Model of Integrating Renewable Distributed Generation into Bali’s Power Distribution Systems: Issues, Challenges, and Possible Solutions - Ngakan Putu Satriya Utama; Rukmi Sari Hartati; Wayan G. Ariastina; Ida Bagus A. Swamardika; Ontoseno Penangsang (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Spurred by a global energy crisis, the use of renewable distributed generation (DG) with solar photovoltaic (PV) energy, micro-hydro power, and biomass power are gaining momentum and play major role in Bali’s distribution system as an alternative distribution system planning option. If distributed generation planning is optimal by selected optimization of multi-objective function under certain operating constraints and then their site and size are also selected optimally, the penetration of DGs is potentially beneficial. This paper would review techno-economic model objective, voltage profile improvement and power losses constraints as well as optimization based model using particle swarm optimization (PSO) algorithm application in Bali’s distributed generation planning.